Competition between Two Isolates of Denitrifying Bacteria Added to Soil - Murray, Robert E. (1992)
We examined the competitive relationship between two isolates of denitrifying bacteria, both of which grow well under aerobic conditions but differ in their ability to grow under denitrifying conditions. The growth and persistence of the two isolates, added to sterile soil or added to soil previously colonized by the other isolate, were monitored under aerobic and denitrifying (anaerobic) conditions. When isolates were added together to sterile soil, the isolate added at the higher density reduced the growth of the isolate added at the lower density. The magnitude of the growth reduction varied depending on the competitive abilities of the individual isolates and the aeration state of the soil. Prior colonization of soil with one of the isolates conferred a competitive advantage on the colonized isolate but did not lead to the disappearance of the challenging isolate. Fluctuations in aeration state caused large changes in the population density of one isolate and altered the competitive relationship between the two isolates. The competitive effectiveness of each isolate varied with cell density, the degree of prior colonization of the soil by the other isolate, and the aeration state of the soil.